Comparative analysis and forecast of spinal cord injury burden in BRICS countries (1990–2021): insights from the Global Burden of Disease Study 2021 - Yuan, Kongjun; Ou, Mengye; Chen, Shaohui; Bai, Tian; Lin, Hailong; Luo, Zhuqiang; Gao, Yanli; Chen, Xiaoqiang; Shi, Sixiong; Zhu, Dan (Frontiers in Public Health, 2025)
BackgroundAs major emerging economies, the BRICS (Brazil, Russia, India, China, and South Africa) face a significant and distinct burden of spinal cord injury (SCI). We systematically assessed trends in the burden of SCI and its leading causes from 1990 to 2021 and forecasted trends to 2031, providing evidence to optimize prevention and control strategies.MethodsBased on the Global Burden of Disease Study 2021 (GBD 2021), we calculated the age-standardized incidence and prevalence rate (ASIR, ASPR) of SCI in the BRICS, along with the estimated annual percentage change (EAPC) and average annual percentage change (AAPC). Furthermore, we analyzed the etiological composition of the SCI burden and developed an autoregressive integrated moving average (ARIMA) model to forecast its trends from 2022 to 2031.ResultsFrom 1990 to 2021, the absolute number of SCI cases rose in all BRICS countries except Russia; however, age-standardized rates (ASRs) fell consistently (EAPC range: −2.15 to −0.13). South Africa demonstrated the most substantial reductions (AAPC: ASIR –1.59, ASPR −1.93), while China showed the modest declines (−0.23 and −0.09, respectively). The burden of SCI varied substantially by age and sex. Males bore a consistently higher burden, with peak risks shifting from younger to older females. The peak number of cases occurred earlier (20–35 years) in Brazil, Russia, and South Africa, but was notably delayed in China and India (50–54 years). The leading causes of SCI across the BRICS included falls (70% of cases in India), road injuries, and self-harm and interpersonal violence (35% of cases in South Africa). Based on ARIMA modeling, a continued decline in ASRs is projected for all member countries over the coming decade.ConclusionThe burden of SCI in the BRICS countries is influenced by demographic, socioeconomic, and policy-related factors. Although ASRs have shown improvement, the absolute number of cases continues to grow. This trend necessitates tailored preventive strategies that address specific age, sex, and etiological factors, supported by enhanced international health cooperation, to mitigate the global burden of SCI.